The Use of Hello Talk Application for Speaking Skills: A Case Study of Online Language Learners for Senior High School - Ida Rosilah; Siti Maria Ulfa (Prodi Pendidikan Bahasa Inggris, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Islam Darul Ulum Lamongan*, 2024)
In today's modern era, technological developments have brought many changes, even technology has also spread to the world of education. One of them is the technology of learning English this technology is known as Hello Talk the use of this application is also one of the impacts of the existence of technological developments. Hello Talk is an application to learn various languages, especially English. This research aims to find out how students use the Hello Talk application as a learning medium for English speaking skills this research is conducted online and the intended subjects are high school students who have long used the Hello Talk application as a learning media. This research is qualitative research and the data collection technique used by the researcher was the interview technique, the interview here involves 4 high school 11th-grade students. The results of this study indicate that the Hello Talk application can help students to practice speaking skills. Students stated that they preferred the teacher to use code-switching during class activities, even though they thought it to be relatively difficult to accomplish. In order to improve the learning process, they also suggested incorporating extra resources like online platforms and applications and encouraged engaged conversation in pairs or groups about their various subjects of study. In addition, the use of the Hello Talk application also has many features that can help develop students' speaking skills, such as Voice Room, Talking with native speakers, Calls, and voice notes.